School Bullying Among Left-Behind Children: The Efficacy of Art Therapy on Reducing Bullying Victimization - Yan, Hu; Chen, Jindong; Huang, Jing (Frontiers in Psychiatry, 2019)
Background: Left-behind children (LBC) are becoming a widespread phenomenon and face higher risks of psychological and educational problems. Our study aimed to explore school bullying in LBC and examine the effectiveness of art therapy intervention for reducing bullying victimization affecting LBC in rural areas. Methods: A total of 603 children, including 272 LBC and 331 non-LBC, were sampled from 6 rural schools. Questionnaires regarding school life satisfaction, children’s social anxiety, self-esteem, and school bullying were used to assess the psychological and school behavior status of these children. 180 LBC who were victims of school bullying were then selected and randomly assigned to 3 groups to evaluate the effects of art therapy intervention. The interventions of art therapy and general counseling were conducted in 6 sessions over 3 months. Results: Our results demonstrated LBC experienced more bullying victimization than non-LBC. Left-behind boys were more likely to be bullied than left-behind girls. LBC>12 years old, LBC whose parents are divorced, separated, or widowed, were more vulnerable to being bullied. School bullying of LBC was affected by social anxiety scores and school life satisfaction. The bullying victimization of LBC in the art therapy group was significantly improved. Conclusions: LBC suffered more school bullying than did non-LBC. Art therapy can effectively help LBC in rural primary schools to reduce their vulnerability to bullying.